2008
DOI: 10.1007/s11095-008-9721-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Drug–Polymer Miscibility and Solubility in Amorphous Solid Dispersions Using Experimentally Determined Interaction Parameters

Abstract: Miscibility of various drugs with polymers can be explored by coupling solution theories with experimental data. These approximations provide insight into the physical stability of drug-polymer mixtures and the thermodynamic driving force for crystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
374
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 442 publications
(399 citation statements)
references
References 60 publications
15
374
0
2
Order By: Relevance
“…Close examination of the table underlines the importance of the various factors that have been implicated in determining the phase behavior of ASDs containing a hydrophobic API following exposure to moisture: hygroscopicity of the ASD system (6), hydrophobicity of the API (7), and the strength of API-polymer interactions (7,8,17). Hence, previous studies have shown that ASDs prepared with a less hygroscopic polymers, for example HPMCAS, are in general, less susceptible to moisture induced amorphous-amorphous phase separation (3).…”
Section: Discussionmentioning
confidence: 99%
“…Close examination of the table underlines the importance of the various factors that have been implicated in determining the phase behavior of ASDs containing a hydrophobic API following exposure to moisture: hygroscopicity of the ASD system (6), hydrophobicity of the API (7), and the strength of API-polymer interactions (7,8,17). Hence, previous studies have shown that ASDs prepared with a less hygroscopic polymers, for example HPMCAS, are in general, less susceptible to moisture induced amorphous-amorphous phase separation (3).…”
Section: Discussionmentioning
confidence: 99%
“…Phase diagrams for CBZ and polymer systems were generated using Flory-Huggins Theory as previously described (20)(21)(22)(23)(24)(25)(26). Briefly speaking, the Gibbs free energy of mixing function that results from application of the FloryHuggins model is dependent on the volume fraction of the drug, ϕ, a constant indicative of the relative size of the polymer in relation to the drug, m, and the interaction parameter, χ:…”
Section: Modeling Based On Flory-huggins Theorymentioning
confidence: 99%
“…Secondly, the molten drug and polymer are uniformly mixed. Thirdly, the molten mixture is cooled down to room temperature to get a solid product (25)(26)(27). In case of eutectic mixtures, the melting point of the mixture is less than the individual components which means less energy is required for the first step and hence higher solubility and miscibility.…”
Section: Introductionmentioning
confidence: 99%